A Successful Clinical Case Study on Management of Visarpa (AYUSHDHARA, 2023)
“Visarpa” is one of the most common skin disorder which explained in Ayurveda. It is one of the most common disease suffering in present era. The Visarpa which is an active transmitting viral disease causing painful skin rash with acute onset blisters in localised areas. Visarpa is predominantly involved Pitta dosha due to Pitta drava and Sara guna more which spreads easily all over the body. Viral syndrome caused by oraganism named as “varicella zoster”. Incidence of herpes zooster ranges from 3.9 to 11.8 per 1000 person per year. Reoccurrence are most common in patients who is immuno-suppressed. The treatment planned Raktamokshan specially jaloukavacharana which gives very effective results in Visarpa vyadhi. Result of the treatment observed on the basis of improvement in sign and symptoms of Visarpa were found completely healed within 1 week of treatment the detailed case is presented in the following content.